Kearifan Lokal Laut Aceh:Hikmah 60 Hari Pantang Melaut - Nurkhalis, Nurkhalis; Sempena, Iwan Doa (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2018)
Being a country which has thousands of island and even as the world's maritime axis, make Indonesia has abundant marine resources. The marine resource potency is a blessing for local people who work as fishermen. On the other hand, this potency is a disaster due to illegal struggle for excessive looting of marine wealth, exploitation of coral reefs, make the sea to be the easiest route to illegal logging and other criminal practices. This criminalization threatens the sustainability of the marine ecosystem and Indonesian. There have been various policies, government programs from both central and regional to overcome the threats and problems, but the criminals still occur. This study aims to find out what the provisions are of a year from 60 days off without sailing of Aceh local wisdom. As well as what wisdom of 60 days off without sailing of Aceh sea local wisdom. This study uses a descriptive qualitative approach. This article is based on the empirical study, using qualitative perspective by collecting data (in-depth interview and documentation). The study results show that there are 60 days off without sailing such as, on Friday, Eid al-Fitr day, Eid al-Adha day, kenduri laot (sea festival), Independence Day and tsunami day commemoration. In addition, the wisdom of 60 days off without sailing is to provide opportunities for breeding fish and another marine biota, to maintain social relations, to resolve social conflicts, to express of gratitude to God, to remember the services of heroes. It also strengthens faith since Acehnese could practice and maintain a harmonious universe relationship among God the creator, nature and human beings.Keywords: Maritime Axis, Local Wisdom, Aceh Sea, Universe Relations